Microtubule-associated protein 4 forms aggregates consisting of helical filaments - Shuto Miura; Eisuke Ishibashi; Takuto Nakamichi; Koji Uwai; Masahiro Kuragano; Kiyotaka Tokuraku (Biochemistry and Biophysics Reports, 2025)
We previously reported that microtubule-associated protein (MAP) 4 was detected in the cytoplasm as abnormal “puncta” in post-ischemic mouse cardiomyocytes. MAP4, a member of the MAP superfamily, has a repeat region consisting of multiple microtubule-binding sequences in its microtubule-binding domain (MBD), like tau. The tau forms aggregates composed of amyloid fibrils and grows into neurofibrillary tangles in neurons. Therefore, we hypothesized that MAP4 also forms amyloid fibrils in cells. Here, we observed whether MAP4 forms aggregates composed of amyloid fibrils using fluorescence microscopy and transmission electron microscopy with quantum dot (QD) nanoprobes. Since we had previously succeeded in real-time 3D imaging of tau MBD fragment aggregate formation using QD nanoprobes, we attempted to observe aggregates using human MAP4 MBD fragments under the same conditions. Fluorescence microscopy showed that 10 μM MAP4 formed aggregates at a rate similar to that of tau. Time-laps 3D imaging by confocal laser microscopy revealed that MAP4 aggregate grains were smaller in size and the deposits were thinner than tau aggregates. Transmission electron microscopy of the MAP4 aggregates revealed that they consisted of helical filaments with a width of 22.6 ± 2.8 nm and a helical pitch length of 48.2 ± 8.4 nm. The helical filaments of MAP4 were shorter in width and longer in helical pitch than those of tau. Furthermore, MAP4 aggregates did not increase the fluorescence intensity of thioflavin T (ThT), and the circular dichroism (CD) spectrum slightly differed from that of tau. These findings suggest that while MAP4 forms aggregates composed of helical filaments similar to those of tau, the structural properties of these filaments are somewhat distinct.